2017
DOI: 10.4028/www.scientific.net/msf.897.348
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced-Oxidation and Interface Modification on 4H-SiC(0001) Substrate Using Alkaline Earth Metal

Abstract: Enhanced-oxidation of 4H-SiC and interface modification with BaO2 was investigated. The enhanced oxidation of 4H-SiC was drastically dependent on pre-deposited BaO2 thickness. At the oxidation time of 300 min, oxide thicknesses for BaO2 of 2.8 nm and 7.8 nm were 91.8 nm and 26.2 nm, respectively. The physical state of Ba in the oxide was investigated by XPS and 2D-GIXD. At thick BaO2 with a thickness of over 6.4 nm, bridged oxygen and non-bridged oxygen were observed in O1s state. This results shows barium sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…6,7) More recently, gate oxide films containing alkali metals and alkaline earth metals have been reported to show mobility improvement. [8][9][10][11][12][13][14][15][16][17][18][19] In general, metal ions in the gate oxide behave as mobile ions, which causes bias temperature instability. 20) Unlike other elements, it has been reported that Ba, an alkaline earth element, does not behave as a mobile ion because of its large ion size.…”
Section: Introductionmentioning
confidence: 99%
“…6,7) More recently, gate oxide films containing alkali metals and alkaline earth metals have been reported to show mobility improvement. [8][9][10][11][12][13][14][15][16][17][18][19] In general, metal ions in the gate oxide behave as mobile ions, which causes bias temperature instability. 20) Unlike other elements, it has been reported that Ba, an alkaline earth element, does not behave as a mobile ion because of its large ion size.…”
Section: Introductionmentioning
confidence: 99%
“…The SiBa x O y generated at the interface is also considered important for reducing the interface states. [ 18,23 ] Therefore, the gate dielectrics of sample III are mainly composed of SiO 2 and BaO 2 , and a small amount of SiBa x O y compounds, which could effectively improve the quality of the interface. In addition, it is observed from the XPS valence band spectra that the valence band of Ba‐passivated sample III shifts negatively compared with that of sample I, which matches the simulation result of the increased bandgap due to the introduction of Ba.…”
Section: Methodsmentioning
confidence: 99%
“…The thicker BaO 2 layer induced by the higher oxygen content in the mixed environment does not enhance the catalytic oxidation effect. [ 23 ] To maximize the benefits of Ba passivation, it is necessary to precisely control the oxygen content of the mixed atmosphere during annealing. In addition, as the Ba IL of sample II was not oxidized to BaO 2 after Ar annealing, sample II could not obtain reliable data in the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations